Impact of cardiometabolic risk factors on hepatocellular carcinoma incidence in patients with chronic hepatitis B: A retrospective cohort study - Chanavee Toh; Kedsiree Sanit; Pimsiri Sripongpun; Naichaya Chamroonkul; Suthat Liangpunsakul; Teerha Piratvisuth; Apichat Kaewdech (PLoS ONE, 2026)
Background and aims Chronic hepatitis B virus (HBV) infection remains a major global health burden and a leading cause of hepatocellular carcinoma (HCC). While cirrhosis is a well-established risk factor, the contributions of metabolic dysfunction-associated steatotic liver disease (MASLD) and cardiometabolic risk factors (CMRFs) are less clearly defined. This study aimed to evaluate the impact of MASLD and CMRFs on HCC risk in patients with chronic hepatitis B (CHB). Methods We conducted a retrospective cohort study of CHB patients at Songklanagarind Hospital between 2011 and 2021, excluding those diagnosed with HCC within six months of follow-up. Clinical and imaging data were analyzed. Cumulative HCC incidence was estimated using Nelson-Aalen plots. Multivariable Cox regression was used to identify independent predictors. The aMAP score was evaluated in subgroups with obesity, CMRFs, and MASLD. Results Among 4,944 patients, 151 (3.1%) developed HCC. Cirrhosis (adjusted hazard ratio [aHR] 7.22), obesity (aHR 1.85), and male sex (aHR 1.78) were independent risk factors. Statin use (aHR 0.43), higher platelet count (aHR 0.62), and higher albumin (aHR 0.64) were protective. Diabetes and hypertension showed nonsignificant trends, and steatosis and dyslipidemia without statins were not significantly associated with HCC. Risk increased with the number of CMRFs. The aMAP score showed good discrimination in patients with obesity (C-index 0.82), CMRFs (0.79), MASLD (0.74), and in the non-cirrhotic MASLD and non-MASLD (0.69 and 0.71, respectively). Conclusions Cirrhosis, male sex, and obesity were key HCC risk factors. The aMAP score effectively stratified HCC risk among metabolically at-risk CHB patients.